PENGARUH PENURUNAN OMZET PEDAGANG KAKI LIMA DI MASA PANDEMI COVID-19 DI PASAR GEDHE SOLO - Brilian Agung Nugroho; Muhammad Jalari (Jurnal Cakrawala Ilmiah, 2023)
Late 2019 was the start of the Covid-19 pandemic which resulted in a lot of pressure on the wider community, especially street vendors in Solo. This restriction causes street vendors to experience a decrease in turnover in terms of the buying and selling power of the products being promoted. In this study the aim is to find out how the influence of the decrease in turnover of street vendors during the Covid-19 pandemic at Pasar Gedhe Solo. In this study the method used is quantitative method with multiple linear regression analysis. The data collected by the researchers were 57 samples from a total population of 131 street vendors using a questionnaire. This research gives the result that product quality affects the turnover received by street vendors and variable X in explaining variable Y is only 28%. This shows that as much as 72% is influenced by variables that are outside this study.